Python geospatial analysis essentials : process, analyze, and display geospatial data using Python libraries and related tools - Westra, Erik (Community experience distilled., 2015)
If you are an experienced Python developer and wish to get up-to-speed with geospatial programming, then this book is for you. While familiarity with installing third-party Python libraries would be an advantage, no prior knowledge of geospatial programming is required.